The impact of using genotyped reagent red blood cells in antibody identification - Rink, Gabriele; Scharberg, Erwin; Portegys, Jan; Bugert, Peter (Transfusion medicine and hemotherapy, 2018)
Background: The detection and identification of antibodies to red blood cell (RBC) antigens is one of the most important and challenging issues in transfusion medicine. Up to date there are 354 RBC antigens recognized by the International Society of Blood Transfusion (ISBT). The reagent RBCs used in commercial antibody screening and identification panels however are usually serologically typed for up to 40 clinically important antigens. Thus the identification of many antibody specificities remains impossible when using reagent RBCs with only limited information about their antigens. To improve the pre-transfusion diagnostics, we developed antibody identification panels with reagent RBCs serologically typed for 26 antigens and additionally genotyped for 30 blood group alleles. Methods: The reagent RBCs in the panels were characterized serologically for the clinically most significant ‘standard’ antigens. The reagent RBC donors were additionally genotyped by using in-house PCR-SSP methods. The antibody identification was performed in the indirect antiglobulin test using untreated and papain-treated RBCs in the gel technique. Antibodies dentified due to the genotype information were confirmed by serology using appropriate reference RBCs. Results: Within a time period of 3 years and 8 months, 16,878 blood samples from 8,467 patients were tested in our reference laboratory. In total, 21 different antibodies. from 10 different blood group systems could be identified in 126 patients (1.5%) due to the genotype information obtained for the reagent RBCs. Antibodies to antigens from the Knops system (53 patients; 42%, 8 patients with anti-Knb) and to Cartwright antigens (31 patients; 25%) were the most frequent. Conclusion: The use of genotyped reagent RBCs in antibody identification panels extends the range of detectable antibody specificities, accelerates the antibody identification, and improves the pre-transfusion diagnostics.
Gesehen am 28.05.2019